How Dreams Are Driven: An Analysis of Advocacy Coalition Framework on Khon Kaen’s Light Rail Transit Project in Thailand - Pholsim, Suriyanon (Journal of Public Administration, Public Affairs, and Management, 2021)
This study integrates the Advocacy Coalition Framework (ACF) to analyze how the winning coalition drives their desired policy— the light rail transit (LRT) in Khon Kaen City, Thailand. This study also combines ACF’s three-tiered belief structure to examine actors’ types and roles based on ACF’s actor ideal among diversified coalitions in LRT’s policy subsystem. This study is conducted based on a qualitative methodology that depends on two data sources—primary data from previous filed works and interviews and the author’s experience working with the Khon Kaen coalition. The analytical framework for this empirical case is grounded on content analysis following the ACF ideal. The results show that there are two main coalitions within LRT’s policy subsystem—Khon Kaen’s local coalition and the central bureaucrat coalition. Khon Kaen’s coalition desires to drive their beliefs—solving traffic issues and advance their homeland, through the first LRT project that locally and fully owns by the five local governments in Khon Kaen City. However, the LRT project involves various ministries or overlapping authorities with the central bureaucrat coalitions—the Ministry of Transportation (MOT), Ministry of Finance (MOF), Ministry of Agriculture and Cooperatives (MOAC), and Ministry of Interior (MOI) who try to centralize the authority. Nonetheless, the Khon Kaen coalition changes strategies to push the project forwards through external events—national mood and open political climate to network and dialogue with top-rank national politicians. The project finally gets approval in 2019 after a decade of works among the coalitions. This study classifies three actors in LRT’s policy subsystem based on the ACF: principal actors—KKTT, KKTS, MOT, MOF, MOAC, and MOI, policy brokers—national top-rank politicians, and auxiliary actors—civil society organization and residents.